Evaluation Of Toothache Activity Of Methanolic Extract And Its Various Fractions From The Leaves Psidium Guajava Linn - S. JAYAKUMARI; J. ANBU; V. RAVICHANDIRAN; S.NITHYA; ASHWINI ANJANA; D. SUDHARANI (International Journal of Pharma and Bio Sciences, 2012)
Psidium guajava L is commonly known as guava in English. The present investigation focuses on the toothache activity. The investigation is based upon the analgesic, anti-inflammatory and anti-microbial activity of water extract of Psidium guajava L. The study assessed the different solvent extracts of Psidium guajava leaf for thin layer chromatography (TLC) and also evaluated the analgesic activity by Hot plate and acetic acid induced writhing, anti-inflammatory action by Invitro HRBC membrane stabilization method and antimicrobial activity by Disc diffusion method, Agar well diffusion method and Minimum inhibitory concentrations (MIC) in animal model. The present preliminary study demonstrated marked toothache activity of Psidium guajava leaf. These results support the notion that plant flavonoids and extracts may have many roles as pharmaceuticals.